RELATIONSHIP OF CLASS ACTION MANAGEMENT TOWARD INDONESIAN LEARNING OUTCOMES: (Hubungan Manajemen Tindakan Kelas Terhadap Hasil Belajar Bahasa Indonesia) - Yusnan, Muhammad; Wulandari, Wulandari (Uniqbu Journal of Social Sciences, 2021)
Improving the quality of education will be achieved if the teaching and learning process by the teacher held in the classroom is truly effective and useful for achieving the expected knowledge, attitudes and skills. Because basically the teaching and learning process is the core of the overall education process, while the teaching and learning process is carried out in many formal activities in the classroom where the teacher is one of the important factors in determining the success of the teaching and learning process in the classroom. Therefore teachers are required to be able to improve their roles and competencies, competent teachers will be more able to create an effective learning environment and will be more capable of Classroom Action Management so that student learning outcomes are at an optimal level. The purpose of this study was to determine the effect of classroom action management on Indonesian learning outcomes, the subject of story listening skills in SD Negeri 1 Kaobula. The method used in this research is quantitative descriptive which is used as a research design that clearly and clearly describes the research variables in the form of numbers and statistics. The population of this research is this research is the fifth grade students of SD Negeri 1 Kaobula which consists of 24 students. Based on the results of the study, it is concluded that the influence between the X variable (classroom action management) and the Y variable (Civics learning outcomes) has a strong influence between the two variables. If we look at the amount of rxy obtained, namely: 0, 620 it turns out to be between 0.40. 0.60. It can be stated that the correlation between variable X and variable Y is a relatively strong influence. Thus, the authors can simply give an interpretation of the rxy, namely that there is a significant positive effect between variable X and variable Y. Keywords: Education, Kemuhammadiyahan, Character